Exploring the Importance of EFL Teachers’ Weekly Pedagogical Workshop on the Teaching Performance in EFL Advanced Classes: Case Studies of Some Secondary Schools in Ouémé Region - TEBA, Sourou Corneille (My University, 2021)
In order to make Beninese English teachers aware that they have an important part to play in their professional growth, authorities in charge of education have suggested amongst many activities, weekly pedagogical workshops (WPW). These meetings are directed by one or two head-teachers elected by their peers. This paper aims at surveying teachers’ attendance rate, the different programs carried out during the sections, the subjects discussed and the rationale for weekly pedagogical workshop viewed from teachers’ standpoint. To achieve this goal, questionnaires were distributed to twenty (20) teachers, and a series of teachers’ weekly meetings observation was carried out. Experimentation based on classroom observations has been carried out with twenty (20) teachers in Porto-Novo. The results showed that teachers express low interest in the weekly pedagogical workshop. This is shown through the low rate of attendance, due to monotony or lack of innovation in the meeting agendas and the paucity of information and discussion about teachers’ classroom practices.
Keywords: WPW; teaching experiences; reflection; classroom performance; CPD